13C Urea Breath Test for Helicobacter pylori: Determination of the Optimal Cut-Off Point in a Canadian Community Population. (2006) - Mauro, Marina; Radovic, Vladimir; Zhou, Pengfei; Wolfe, Melanie; Kamath, Markad; Bercik, Premsyl; Croitoru, Ken; Armstrong, David
Abstract : AIM: To determine the test characteristics and the optimal cut-off point for the 13 C urea breath test ( 13 C UBT) in a Canadian community laboratory setting. METHODS: Of 2232 patients (mean age ± SD: 51±21 years, 56% female) who completed a 13 C UBT, 1209 were tested to evaluate the primary diagnosis of Helicobacter pylori infection and 1023 were tested for confirmation of eradication following treatment. Cluster analysis was performed on the 13 C UBT data to determine the optimal cut-off point and the risk of false-positive and false-negative results. Additionally, 176 patients underwent endoscopic biopsy to allow validation of the sensitivity and specificity of the 13 C UBT against histology and microbiology using the calculated cut-off point. RESULTS: The calculated cut-off points were 3.09 δ‰ for the whole study population (n=2232), 3.09 δ‰ for the diagnosis group (n=1209) and 2.88 δ‰ for the post-treatment group (n=1023). When replacing the calculated cut-off points by a practical cut-off point of 3.0 δ‰, the risk of false-positive and false-negative results was lower than 2.3%. The 13 C UBT showed 100% sensitivity and 98.5% specificity compared with histology and microbiology (n=176) for the diagnosis of active H pylori infection. CONCLUSIONS: The 13 C UBT is an accurate, noninvasive test for the diagnosis of H pylori infection and for confirmation of cure after eradication therapy. The present study confirms the validity of a cutoff point of 3.0 δ‰ for the 13 C UBT when used in a large Canadian community population according to a standard protocol.